2018
DOI: 10.1177/0091415017752936
|View full text |Cite
|
Sign up to set email alerts
|

The Complexities of Family Caregiving at Work: A Mixed-Methods Study

Abstract: The current project examined the impact of caregiving and caregiving-work conflict on employees' well-being. A sequential explanatory mixed-methods design (QUAN→qual) was utilized, and a total of 880 employees from a large health-care plan employer completed an online survey. Forty-five caregivers who completed the survey also participated in one of the five focus groups held 1 to 2 months later. Employed caregivers were significantly ( p < .05) more likely to indicate poorer physical and mental health than no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 61 publications
(59 reference statements)
0
33
1
2
Order By: Relevance
“…Costs of dementia caregiving for employers may include replacement costs for employees who quit due to their caregiving responsibilities and costs of absenteeism and workday interruptions 404 . In 2010, employers lost $13 billion due to employees’ elder care responsibilities 405,406 …”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…Costs of dementia caregiving for employers may include replacement costs for employees who quit due to their caregiving responsibilities and costs of absenteeism and workday interruptions 404 . In 2010, employers lost $13 billion due to employees’ elder care responsibilities 405,406 …”
Section: Caregivingmentioning
confidence: 99%
“…404 In 2010, employers lost $13 billion due to employees' elder care responsibilities. 405,406 In 2019, it is estimated that dementia caregivers bore nearly twice the average out-of-pocket costs (for example, medical care, personal care and household expenses for the person with dementia and personal expenses and respite services for the caregiver) of non-dementia caregivers ($11,372 versus $6,121). 407 Data from the 2016 Alzheimer's Association Family Impact of Alzheimer's Survey indicated that among care contributors (a friend or relative who paid for dementia expenses and/or provided care for someone with dementia at least once a month in the prior year), 48% cut back on spending and 43% cut back on saving due to the out-of-pocket costs of providing help to someone with dementia.…”
Section: Caregiver Employment and Financesmentioning
confidence: 99%
“…(Very good, Good, Neither good nor poor, Poor, Very poor); and (5) I nd comfort in my religion or spirituality many times a day, every day, most days, some days, once in awhile, never/almost never, not applicable. As reported previously [8], we also asked questions about retirement and included one of those questions in the current analyses -Have you thought about or begun to think about retiring from full-time employment in academic medicine? (Yes, Unsure -maybe 5 years, Unsure -maybe 10 years, No).…”
Section: Methodsmentioning
confidence: 99%
“…Caregiving and caregiving burden affect employee wellness and productivity [8][9]. With increased awareness of both current and projected growth in caregiving responsibilities among their faculty members, human resource and faculty affairs and development leaders may develop appropriate policies, programs, and resources.…”
mentioning
confidence: 99%
“…Previous research suggests that employed caregivers experience more strain when reporting high levels of primary caregiving stressors and high levels of caregiving to work conflict (CWC), such as having to adjust hours or perform caregiving duties from work (Barling, MacEwen, Kelloway, & Higginbottom, 1994; Fredriksen-Goldsen & Scharlach, 2006; Gaugler et al, 2018; Longacre, Valdmanis, Handorf, & Fang, 2016; Reid, Stajduhar, & Chappell, 2010). However, less is known about how organizational factors, such as supervisor disclosure and caregiver-friendly workplace policies (CFWPs), may diminish the impact of CWC on caregiver strain.…”
mentioning
confidence: 99%